Settlement Discontinuity and Resistance to Complexity in Cyprus, ca. 4500-2500 B. C. E - Peltenburg, Edgar (Bulletin of ASOR, 1993)
This article presumes that small prestate societies possessed fluctuating asymmetrical political relationships and that those relationships may have left material correlates in the archaeological record. Settlement discontinuity in the Neolithic and Chalcolithic periods of Cyprus may be due in part to recurrent community fissioning caused by resistance to attempts by subgroups to extend power. Following Trigger (1990: 145), a brief attempt is made to isolate and assess those new features that eventually eroded resistance to the establishment of stratified society.